2020
DOI: 10.1111/febs.15473
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule‐associated proteins and emerging links to primary cilium structure, assembly, maintenance, and disassembly

Abstract: The primary cilium is a microtubule‐based structure that protrudes from the cell surface in diverse eukaryotic organisms. It functions as a key signaling center that decodes a variety of mechanical and chemical stimuli and plays fundamental roles in development and homeostasis. Accordingly, structural and functional defects of the primary cilium have profound effects on the physiology of multiple organ systems including kidney, retina, and central nervous system. At the core of the primary cilium is the microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 91 publications
(135 reference statements)
0
29
0
Order By: Relevance
“…Regulation of ciliogenesis is a complex process involving multiple factors directly or indirectly influencing cilia initiation and elongation. The regulators of cilium formation encompass a wide range of molecules such as components of centrioles, regulators of vesicular trafficking, intraflagellar transport proteins, membrane proteins, and components of cytoskeleton (Seeley and Nachury, 2010;Ishikawa and Marshall, 2017;Wang and Dynlacht, 2018;Conkar and Firat-Karalar, 2020). WNT3a is considered a prototypical "canonical" WNT ligand that activates WNT/β-catenin pathway (Willert et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of ciliogenesis is a complex process involving multiple factors directly or indirectly influencing cilia initiation and elongation. The regulators of cilium formation encompass a wide range of molecules such as components of centrioles, regulators of vesicular trafficking, intraflagellar transport proteins, membrane proteins, and components of cytoskeleton (Seeley and Nachury, 2010;Ishikawa and Marshall, 2017;Wang and Dynlacht, 2018;Conkar and Firat-Karalar, 2020). WNT3a is considered a prototypical "canonical" WNT ligand that activates WNT/β-catenin pathway (Willert et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of ciliogenesis is a complex process involving multiple factors directly or indirectly influencing cilia initiation and elongation. The regulators of cilium formation encompass a wide range of molecules such as components of centrioles, regulators of vesicular trafficking, intraflagellar transport proteins, membrane proteins and components of cytoskeleton (Wang and Dynlacht 2018; Conkar and Firat-Karalar 2020; Ishikawa and Marshall 2017; Seeley and Nachury 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale proteomic studies have revealed that there are more than 400 centrosome-associated proteins (about 3% of human proteome, but the exact functions of most of these proteins are still unknown and require further investigation. However, recent advances in imaging, proteomics, and structural biology have revealed new insights into how microtubule-associated proteins regulate the structure, length, and stability of centrosome/cilium complex opening up new avenues for future research [ 8 , 26 , 27 , 28 ].…”
Section: Centrosome Biology and Cinmentioning
confidence: 99%
“…Shared pathways ensure the coordination between centrosome dynamics, chromosome replication–segregation cycles, and ciliogenesis. Details on the centrosome/cilia dynamins can be found in recent excellent reviews [ 8 , 21 , 23 , 26 , 27 ]. ( B ) Excess of expression of centrosome genes (structural changes) can disrupt apical cell extrusion, instead, causing aberrant basal extrusion.…”
Section: Figurementioning
confidence: 99%